2017
DOI: 10.1097/bsd.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Watertight Sealing Without Lumbar Drainage for Incidental Ventral Dural Defect in Transthoracic Spine Surgery

Abstract: The established watertight closure of the dural defect using the triple layer sealing method without lumbar drainage was more effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However in the cases of anterior cervical surgery, there are not enough muscles for coverage of cervical vertebrae, swallowing and coughing can cause CSF pressure fluctuation. So the effect is poor in anterior cervical region 16, 24…”
Section: Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However in the cases of anterior cervical surgery, there are not enough muscles for coverage of cervical vertebrae, swallowing and coughing can cause CSF pressure fluctuation. So the effect is poor in anterior cervical region 16, 24…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…In this review, all treatment approaches were classified into two groups based on a fluid flow mechanics: 1) stopping CSF leak by direct suture or augmented closure with dural substitute material 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ; 2) retarding CSF leak by reducing the subarachnoid fluid pressure and/or increasing the epidural space pressure. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 …”
Section: Treatment Strategiesmentioning
confidence: 99%
“… 67 69 We and others have also shown that fibrin supports neural progenitor survival in vivo 16 , 70 , 71 and can provide physical and trophic support for nervous tissue ingrowth in neural tissue engineering models. 72 , 73 The safety and efficacy of fibrin glue (Tisseell; Baxter, Deerfield, IL) as a watertight sealant in neurosurgical applications have already been established, 74 and the potential of fibrin hydrogels as a delivery vehicle for donor neural cells and growth factors represents another advantage as a substrate for MMC repair. 75 , 76 Desirable properties for any hydrogel suitable for fetal MMC surgical repair include rapid transition from liquid to solid phase, impermeability in the aqueous in utero environment, favorable attachment to surrounding tissues, and biocompatibility with fetal neural elements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies did not classify the use of a fibrin sealant according to the completeness of the dural closure 3 4 6 7 13 24 25) . Frequently, the incidental durotomy margin is uneven, and a watertight dural closure could not be completed with only suture.…”
Section: Discussionmentioning
confidence: 99%